Molecular analysis of mitogen-activated protein kinase signaling pathways induced by reactive oxygen intermediates - Schmitz, Lienhard; Bacher, Susanne; Dröge, Wulf (Redox cell biology and genetics ; A: Redox cell biology and genetics, 2002)
The chapter describes methods to measure mitogen-activated protein kinase (MAPK) phosphorylation and activity induced by changes in the thiol state or by reactive oxygen intermediates (ROIs). Depending on the cell type, approximately 1-20 x 106 cells are stimulated. The family of MAPKs consists of three groups, they are: cJun N-terminal kinases (JNKs), p38 MAPKs, and extracellular signal-regulated kinases (ERKs). MAPKs are activated by dual phosphorylation at conserved threonine and tyrosine residues by MAPK kinases (MAPKKs), which in turn are substrates for MAPK kinase kinases (MAPKKKs). ROIs can affect all three MAPK signaling pathways, but the concentration and chemical structure of reactive oxygen species, the cell type, and the physiological context determine which MAPK is activated. In-gel kinase assays are employed when specific antibodies for the kinase are unavailable or when the identity of the kinase is unknown. Cells are incubated with the inhibitory compound followed by the investigation of redox-induced MAPK activity either by Western blotting using phospho-specific antibodies or by kinase assays.